Phosphate based glass thin films for biofilm prevention in orthopaedic implants - Thomas, Kathryn G. (2020)
Biofilm infections affect 1-4% of orthopaedic implants, causing cyclical chronic pain for the affected patient and an estimated cost in the UK of around £2 billion annually [1]. Phosphate based glasses (PBGs) have been widely demonstrated to degrade in aqueous media and can be deposited in highly adherent thin films on a large range of substrates using Radio-Frequency Magnetron Sputtering (RFMS). Ga3+ has been widely investigated for its antimicrobial effects against a wide range of pathogens at <9 mM [2][3]. This work aimed to produce high Ga2O3 content coatings for rapid Ga3+ release in vivo, and to determine whether an unstable surface could prevent bacterial attachment or whether rapid ion release could produce an antimicrobial effect while being tolerated by human osteoblasts. Co-sputtering of non-Ga2O3 doped PBG targets and a pure Ga2O3 ceramic target successfully produced two films: (P57ˑFe3(150):Ga2O3(50) and P45ˑFe0(150):Ga2O3(50)) which were reported to contain 41.5 ± 0.4 and 30.6 ± 0.5 mol% Ga2O3 respectively. These are the highest Ga2O3 content PBG structures reported in the literature. Transmission Electron Microscopy (TEM) analysis showed that the P57ˑFe3(150):Ga2O3(50) was fully amorphous and can therefore be considered to have been successfully deposited as a glass structure. Both glass composition and film thickness were found to influence film degradation. The presence of Fe2O3 in the films at amounts as low as 1.2 mol% was found to be enough to fully stabilise the glass in DMEM. The thickness of the film was also shown to have an effect on whether full degradation was achieved, as while the 36 nm thick P45ˑFe0(150) film degraded fully, the P45ˑFe0(150):P45ˑFe0(150) film of 447 nm thickness degraded initially but then stabilised in the DMEM, despite having no significant differences in composition. By sputtering a composition without Fe2O3 one film doped with Ga2O3 was produced which successfully degraded within 24 h (P45ˑFe0(150):Ga2O3(50)). Microbiological assays showed that none of the films had a significant impact on the volume of bacteria which were able to adhere to the sample surface over 6 h, showing that more rapid degradation rates are needed. The concentration of Ga3+ eluted into the media was not sufficient to significantly perturb the growth of clinically relevant bacteria. Further investigation suggested that a degrading film would need to create a local Ga3+ concentration in excess of 1.1 mM in order to achieve the desired antimicrobial effect. 24 h exposure to 1.1 mM of Ga3+ was shown to have a cytotoxic effect on human osteoblast-like cells. However, by reducing the exposure time to 6 h to simulate an “ion burst” effect (which could be achieved with a rapidly degrading film) the effect on cells was no longer classed as cytotoxic. After 14 d culture to allow the cells to recover, metabolic levels were similar to that of untreated cells. Human cell culture studies on substrate surfaces after complete film degradation showed no difference in cellular colonisation of the surface post-degradation compared to an untreated control substrate.